Pulsed electron avalanche knife: new technology for cataract surgery. Issue 7 (17th January 2007) - Priglinger, Siegfried G; Palanker, Daniel; Alge, Claudia S; Kreutzer, Thomas C; Haritoglou, Christos; Grueterich, Martin; Kampik, Anselm
Abstract : Background: The pulsed electron avalanche knife (PEAK-fc) is a new pulsed electrosurgical device that allows for precise, "cold" and traction-free tissue dissection. Aim: To evaluate the surgical applicability, safety and potential complications of PEAK-fc in complicated cataract surgery. Methods: The study included five children with congenital cataracts, two patients with advanced senile cataracts, six adults with mature cataracts, three of them with posterior iris synechia, three patients with post-traumatic cataracts with zonulolysis, one patient with intumescent traumatic cataract and three patients with massive anterior capsule opacification. Anterior and posterior capsulotomies, iris synechiolysis, dissection of anterior capsule opacification and fibrotic scar tissue were performed. PEAK-fc was set at voltages of 500–700 V, pulse duration of 0.1 m and repetition rate of 40–100 Hz. Results: Anterior and posterior capsulotomies were successfully and safely performed in all eyes. The edges of capsulotomies appeared sharp, showing only limited collateral damage. PEAK-fc worked best by just gently touching the capsule, thereby avoiding tractional forces or pressure on the lens capsule. Posterior iris synechiae could be released and anterior capsule opacification was dissected without complications. Conclusions: PEAK-fc is a very helpful cutting device for complicated cases of cataract surgery, especially for mature and congenital cataracts, traumatic zonulolysis or anterior segment complications after intraocular inflammation.